Under British Eyes: The Complex Fortune of Italian Crime Fiction (Altre Modernità, 2010)
Under British Eyes: The Complex Fortune of Italian Crime Fiction(Mirna Cicioni & Nicoletta Di Ciolla (eds), Differences, Deceits and Desires. Murder and Mayhem in Italian Crime Fiction, Newark: University of Delaware Press, 2008, 228 p., ISBN 978-0-87413-051-5)by Nicoletta Vallorani